2022
DOI: 10.1093/jscr/rjac066
|View full text |Cite
|
Sign up to set email alerts
|

Tension offloading improves cutaneous scar formation in Achilles tendon repair

Abstract: Hypertrophic scar formation and non-healing wounds following Achilles tendon repair arise from poor vascularity to the incisional site or from excess mechanical stress/strain to the incision during the healing process. The embrace® scar therapy dressing is a tension offloading device for incisional scars. This study explored the effects of tension offloading during Achilles scar formation. A healthy 30-year-old male without any medical co-morbidities developed an acute rupture of his left Achilles tendon. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A related study using CO 2 fractional laser to control scar growth after skin cancer surgery found that the CO 2 fractional laser was effective in controlling scar thickness and flexibility. 15 Furthermore, studies have shown that the use of tension-reducing devices such as tension-reducing tape 16 and tension reducers 17 , 18 are also clinically effective in inhibiting postoperative scar growth. These devices not only reduce the thickness of the scar, but also the width of the scar.…”
Section: Discussionmentioning
confidence: 99%
“…A related study using CO 2 fractional laser to control scar growth after skin cancer surgery found that the CO 2 fractional laser was effective in controlling scar thickness and flexibility. 15 Furthermore, studies have shown that the use of tension-reducing devices such as tension-reducing tape 16 and tension reducers 17 , 18 are also clinically effective in inhibiting postoperative scar growth. These devices not only reduce the thickness of the scar, but also the width of the scar.…”
Section: Discussionmentioning
confidence: 99%
“…Tension is one of the major causes of HS formation, and persistent tension in the lesion is more likely to cause HS formation. 25 The most common clinical locations for HS are in the chest, back, and joint motion areas with high tension. Because of persistent tension, HSs in these areas are more likely to recur after treatment.…”
Section: Fractional Co 2 Laser Combined With Btxa Injection Inhibited...mentioning
confidence: 99%